MicroRNAs and other small RNAs in Aedes aegypti saliva and salivary glands following chikungunya virus infection - Carmine Fiorillo; Pei-Shi Yen; Alessio Colantoni; Marina Mariconti; Nayara Azevedo; Fabrizio Lombardo; Anna-Bella Failloux; Bruno Arcà (Scientific Reports, 2022)
Abstract Mosquito saliva facilitates blood feeding through the anti-haemostatic, anti-inflammatory and immunomodulatory properties of its proteins. However, the potential contribution of non-coding RNAs to host manipulation is still poorly understood. We analysed small RNAs from Aedes aegypti saliva and salivary glands and show here that chikungunya virus-infection triggers both the siRNA and piRNA antiviral pathways with limited effects on miRNA expression profiles. Saliva appears enriched in specific miRNA subsets and its miRNA content is well conserved among mosquitoes and ticks, clearly pointing to a non-random sorting and occurrence. Finally, we provide evidence that miRNAs from Ae. aegypti saliva may target human immune and inflammatory pathways, as indicated by prediction analysis and searching for experimentally validated targets of identical human miRNAs. Overall, we believe these observations convincingly support a scenario where both proteins and miRNAs from mosquito saliva are injected into vertebrates during blood feeding and contribute to the complex vector–host–pathogen interactions.